On the Front Lines of Implementing Environmental Regulation: The Perspective of the Regulated Community in Montana. Issue 3 (9th April 2018) - Rinfret, Sara; Pautz, Michelle C.
Abstract: Although discussions about environmental policy often focus on the federal level of decision making and action in the United States, implementation occurs predominately at the state level. The individuals largely responsible for implementation are the state regulators and members of the regulated community as they constitute the front lines in environmental regulation. Much of the existing research on regulatory interactions investigates the regulatory enforcement styles of regulators and the compliance motivations of firms. It is equally important to consider the perceptions and actual experiences of regulated community members. To examine this perspective, this exploratory study utilizes a mail survey to investigate the perceptions and experiences of members of the regulated community in Montana. The survey respondents report positive and cooperative interactions with environmental regulators. This survey provides much‐needed insight into the perspectives of some members of the regulated community, challenging traditional viewpoints that the regulated community is hostile toward regulation, and promotes adversarial relationships with regulators. Accordingly, this research encourages debate about the fundamental assumptions surrounding the interactions of regulators and the regulated community in U.S. environmental policy.